Biological Studies of Harmala peganum Exracts as Antibacterial Agent - Tayeb, Ahmed Y. (Scientific Journal for Faculty of Science-Sirte University, 2022)
Harmala peganum is one of the most well-known medicinal plants in traditional Chinese medicine. The goal of this study was to look at the antibacterial effects of a methanol extract of several components of H. peganum, such as the stem and leaf, against certain common human pathogenic bacteria. The antibacterial capabilities of methanol extracts of the specified sections were tested using the disc diffusion method, as well as their synergism activity when combined with synthetic antibiotics. The leaf and stem extracts were the only portions of H. peganum that showed antibacterial action against all of the microorganisms tested, even at the lowest concentrations. Leaf extract out performed stem extract in terms of antibacterial activity against the majority of gram-positive bacteria tested. The extracts were tested for their biological activity against microorganisms such as Streptococcus pneumoniae, Pseudomonas aeruginosa, Salmonella typh, and Escherichia coli. Except for the distilled water extract of H. peganum, the results demonstrated that the extracts are active against all bacterium strains. However, the antibacterial activity of Harmala peganum leaf and stem extracts was higher than that of antibiotics used against the pathogens tested.